IDENTIFYING ERRORS IN A ONE-PHASE ELECTRICAL SYSTEM (International Journal of Engineering Management Science, 2024)
Transmission lines are used to transport electricity to large, distant load centers. These lines can malfunction as a result of lightning strikes, short circuits, broken equipment, overloading, aging, and human error. To avoid this situation, we need the exact location of the fault incidence. In order to cross-check the correctness of a collection of resistors used to indicate cable length in KMs, a group of switches at each known KM causes a fault. Creating a system that can automatically detect a failure in an electrical transmission line and alert the appropriate authorities to its exact position is the only method to address this problem. You will create a contraption with sensors that senses incoming and outgoing values and looks for anomalies during this project. Additionally, the system will be coupled with an Internet of Things method to notify the appropriate parties in real time of the location information. Furthermore, power dissipation in transmission lines, transformers, and other power system components results in natural technical losses. The total load and the total energy bill are used to calculate technical losses in transmission and distribution. As technology advances, we need also be aware of the rise in immoral behavior. The unapproved usage of power is prevented by the technology. With today's technology, the problem of unapproved electricity use can be handled by the Internet of Things without requiring human assistance. The implementation of this technology will conserve a significant quantity of electricity, increasing the number of users in densely populated countries like China and India who have access to electricity. Power theft is the use of electricity without a legitimate contract with the supplier.
Keywords: Internet of Things, LED, DC Fan, Automation, sensors, web application, Data Analysis